Constructing and Standardizing Physical Tests for Speed Endurance In Youth Basketball - Sami, Faris (Journal of Physical Education, 2016)
Basketball is one of the sports that depend on aerobic training in general and on other types of training in particular. Speed endurance is one of the physical fitness components of a basketball player that he needs in performing defensive and offensive skill with high speed. The player needs a lot of time to prepare physically and skillfully to reach to a level that qualifies him to participate in basketball competitions.The subjects of the research were (99) basketball players from (Baghdad, the south region, Middle Forat region) for the season 2015 – 2016. The data was collected using proper statistical operations to come up with the results. The results showed that the test's procedures were standardized for youth basketball players and speed endurance tests were applied for the first time in Iraq for youth basketball players. Finally the researcher concluded finding criteria for speed endurance tests.